Support‐Independent Surface Functionalization for Efficient Pd Loading in Catalytic Hydrogenation. Issue 11 (23rd March 2018) - Fu, Peng; Xiao, Zhourong; Liu, Yanhong; Wang, Li; Zhang, Xiangwen; Li, Guozhu
Abstract: Noble metal catalysts supported on high‐surface‐area supports are of great importance as heterogeneous catalysts in numerous industrial processes. Control of the nanostructures and distribution of metal nanoparticles (NPs) is a key to achieving high activity. Surface functionalization has received much attention for efficient loading of metal NPs. In this study, surface functionalizations of various supports including SBA‐15, Al2 O3, reduced graphene oxide (RGO), and carbon nanotubes (CNTs) have been carried out to facilitate palladium loading. The as‐synthesized supported palladium (Pd) catalysts have been studied by evaluating their catalytic activity for 4‐nitrophenol (4‐NP) hydrogenation in water at room temperature. Transmission electron microscopy and energy‐dispersive X‐ray mapping were used to characterize the catalysts. The results show that the strategy of support surface functionalization for Pd loading is generally applicable to various supports and different reactions of hydrogenation. Catalysts with elevated activity in catalytic hydrogenation have been obtained via efficient Pd loading by the surface functionalization of support. Moreover, kinetic study has been conducted on 4‐NP hydrogenation catalyzed by Pd/SAM‐DA‐CNT (Pd nanoparticles supported on CNTs modified by polydopamine and carboxylic acid‐terminated alkanethiol monolayer). The obtained kinetic data are fitted to a Langmuir‐Hinshelwood (L−H) model, and the calculated apparent activation energy of this process is 65.39 kJ mol −1 . Abstract : A support‐independent strategy of surface functionalization using polydopamine and carboxylic‐acid alkanethiol has been systematically investigated for efficient loading of palladium. Various supports, including SBA‐15, Al2 O3, reduced graphene oxide (RGO), and carbon nanotubes (CNT), were studied by evaluating the catalytic activity for 4‐nitrophenol (4‐NP) hydrogenation in water. Kinetic study on the optimal catalysts has been carried out to gain better insight into the mechanism.